Respostas

2014-05-13T13:10:45-03:00
Resolva as equações, sendo U= Q.

a) X/4 (X SOBRE 4) +2= (x-3, sobre 2)

  x                  x-3
-----  +2    =  --------
  4                   2

x  + 8           x - 3
----------- =  --------
    4                2    agora é cruzar

4(x-3) = 2(x+8)
4x - 12 = 2x + 16
4x - 2x = 16 + 12
2x = 28
x = 28/2
x = 14 






b) 50+ (3x - 4) = 2(3x - 4) +26
50 + 3x - 4 = 6x - 8 +26 
3x + 46 = 6x + 18 
3x - 6x = 18 - 46
-3x = -28
x = -28 
     -----
       -3

x =  28
     ------
        3